Step-by-step explanation:
<h3>1. x² + 4 = (x+2)² </h3>
<h3> : x² + 4 = x² + 4 (Yes)</h3>
<h3>2. (2x+6)²= 4(x+3)²</h3>
<h3> : 4x²+36 = 4x² + 36 ( Yes)</h3>
<h3>3. (x-3)(x-3)= (x-9)² (NO)</h3>
<h3>beacause , True statement is</h3><h3> (x+3)(x-3)= (x-9)²</h3>
<h3>4. x²-10x+25 = (x-5)(x+5) (No)</h3>
<h3> : x²-2x+y² = (a-b)(a+b) </h3>
<h3>Therefore, its not true statement!</h3>
Answer:
6 to the power of 2.
Step-by-step explanation:
Recall that whenever you divide exponents with the same base, you subtract the powers, but the base will still be the same. Therefore, 6 to the power of 12 divided by 6 to the power of 10 is 6 to the power of 2. Subtract the powers (exponents) or 12 minus 10, and you get 2. Since the base doesn't change, it is still 6. The solution to this expression is 6 to the power of 2. Hope this helps!
C: 20 m/s
Explanation:
Distance run: 1000m
Time passed: 50s
Distance divided by time equals speed.
1000m / 50s = 20 m/s
Answer:
(x - 2) (x - 6)
Step-by-step explanation:
Factor the following:
x^2 - 8 x + 12
The factors of 12 that sum to -8 are -2 and -6. So, x^2 - 8 x + 12 = (x - 2) (x - 6):
Answer: (x - 2) (x - 6)
C) 5x^2-3x+9 is the answer